Regulasi Emosi Sebagai Pembentukan Ketahanan Mental Untuk Meningkatkan Mutu Produktivitas Kerja Fungsionaris Lembaga Kemahasiswaan - Huwae, Arthur; Rugebregt, Joanne Marrijda (LPM IHDN Denpasar, 2020)
This study is based on the phenomenon of lack of work productivity that occurs in college students who follow the activities of the organization of the student council. College students still lack the proper emotional management to carry out student council activities, thus affecting the process and the work involved. Considering the problem with the organization of student council functionary, it will require interventions to increase the productivity of the work, which is means of emotional regulation training as a form of mental endurance. The purpose of this study is to know the effectiveness of emotional regulation as a mental endurance of the productivity of members the organization of student council functionality. The productivity scale of their functionary work is used to collect pre-test and post-test data. Based on the test of signed-rank on Wilxocon Statistics, there is a value of 3.923 with a significant 0,000 (p<0.05). This means that effective emotional regulation training increases the productivity of the functionality of an individual within who has good emotional regulation, makes the productive person in fulfilling his duties and functions, and able to be a superior resource, synergy, and competitive